ANALISIS WACANA NASKAH PIDATO INTERNASIONAL SBY: TINJAUAN LINGUISTIK KRITIS - , ANGGARA JATU KUSUMAWATI, Dr. F.X. Nadar, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
President Susilo Bambang Yudhoyono (SBY) image building can be represented through many ways, one of them reflected on his international speeches. On this way, argumentation phases in the speeches can form social construct, self-image, public opinion, new meaning and world-view. Based on critical linguistic point of view, word choice, sentence arrangement, and sentence pattern on speeches show a language expertise. This research aims at 1) describing the structure of SBY international speeches, 2) describing text arrangement of SBY international speeches, 3) describing grammar used of SBY international speeches related with self-image building. This research uses critical linguistics approach proposed by Fowler (1979) via Young and Harrison (2004: 3) which focuses on two metafunctions of Systemic Functional Linguistics Halliday, ideational and textual function. The source of data are nine texts of SBYâs international speech in the year of 2011 chosen based on some criteria